Contribution à l'histoire du texte de la version arabe du Discours 40 de Grégoire de Nazianze - Jacques Grand'Henry (Revue des Mondes Musulmans et de la Méditerranée)
A comparison between four manuscripts containing the Arabic version of the Greek discourse 40 of Gregory of Nazianze helps situate the manuscript from Milan within the overall Arabic manuscript tradition : this particular manuscript, dated from the 11th century, predates most of the other manuscripts in the Arabic version by at least two centuries. Nonetheless, it does not constitute an independent version although it is original in many ways. Our comparative linguistic analysis brings to the fore different phenomena of dassicisation, of phenomena which complete our knowledge about Middle Arabic, phenomena about pre-classical syntax, the Syriacisation of the lexicon, inaccuracies in the translation of Greek, caiques of the Greek model without sufficient adaptation to the spirit of the Arabic language. However, out of a certain number of cases, only manuscript Aft has preserved a faithful translation of the original Greek terms. The author of this article is now preparing a complete edition of the Arabic version of discourse 40.